Fıkıh ve Siyaseti Şer’iyye Bağlamında Küresel Helal Belgelendirme Çalışmalarına Eleştirel Bir Bakış / A Critical View on Global Halal Certification Activities in Terms of Fiqh and Siyasah Shar’iyyah - Yalçın, İsmail (Journal of History Culture and Art Research, 2017)
Abstract Halāl is used by Muslims to mean religiously ‘not forbidden,’ ‘permitted,’ and as opposed to concepts like ‘harām’ and ‘makrooh’, similar to the concepts of ‘mubāh’ and ‘jāiz’. While it was easier to distinguish between halal and haram in the pre-industrial era, today it has become much more difficult due to complex products which are a result of innovations through industry and technology and their tremendous outreach. This has led to a loss of confidence in Muslims in the products they buy and increased the number of products whose halalness is doubted. While historically muhtasibs assumed the duty of preserving people’s confidence in markets by inspecting them, nowadays halal certificates are attempting to do the inspection and generate confidence. Although halal certificate activities have been going on and improving for almost half a century, they are not at a level to generate widespread and efficient halal guarantees. Opinion differences in fiqh, differences in institutions of certification, differences in halal certificates and logos, national and international legal gaps, and commercial competition between countries and institutions of certification affect the efficiency of the process negatively. The claim that the halal certificate is the best standard in terms of health, trustworthiness, and hygiene, its contribution to individual and societal religiosity, and the commercial advantages and disadvantages that it provides to Muslims is a remarkable field of inquiry. Öz Müslümanlar için helal, dini bakımdan yasaklanmamış, izin verilmiş manasında kullanılmakta; haram ve mekruh terimine karşıt, mubah ve caiz terimlerine yakın anlamlar ifade etmektedir. Sanayi öncesi dönemde helal ve haramı ayırt etmek günümüze göre daha basit iken günümüzde sanayi ve teknolojinin getirdiği yeniliklerle ortaya çıkan kompleks ürünler ve bu ürünlerin her yere ulaşabilmesi sebebiyle daha zor ve karmaşık hale gelmiştir. Bu durum Müslümanların satın aldığı ürünlere olan güvenini sarsmış ve giderek karşılaşılan helalliği şüpheli ürünlerin sayısını artırmıştır. Tarihte muhtesiplerin pazar denetimi Müslüman halk için bir güvence oluştururken günümüzde bu denetim ve güvence helal belgelendirme yöntemiyle sağlanmaya çalışılmaktadır. Yarım asırdan bu tarafa helal belgelendirme çalışmaları gelişerek devam etmesine rağmen bu çalışmalar henüz etkin ve yaygın bir helal güvence sağlayacak düzeyde değildir. Fıkhi ihtilaflar, sertifika kurumları arasındaki farklılıklar, helal sertifika ve helal logo farklılıkları, ulusal ve uluslararası düzeyde yasal boşluklar, ülkeler ve sertifika kurumları arasında ticari rekabet, uygulamanın etkinliğini olumsuz etkilemektedir. Helal belgesinin sağlıklı, güvenli ve hijyenik en üst ürün güvencesi olduğu iddiası, ferdi ve toplumsal dindarlığımıza yaptığı katkılar ve ticari alanda Müslümanlara sağladığı avantajlar ve dezavantajlar, dikkat çekici bir araştırma alanıdır.